2020
DOI: 10.3390/ijms21020654
|View full text |Cite
|
Sign up to set email alerts
|

HMGA Genes and Proteins in Development and Evolution

Abstract: HMGA (high mobility group A) (HMGA1 and HMGA2) are small non-histone proteins that can bind DNA and modify chromatin state, thus modulating the accessibility of regulatory factors to the DNA and contributing to the overall panorama of gene expression tuning. In general, they are abundantly expressed during embryogenesis, but are downregulated in the adult differentiated tissues. In the present review, we summarize some aspects of their role during development, also dealing with relevant studies that have shed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 295 publications
2
45
0
Order By: Relevance
“…ID2-which modulates bone morphogenetic protein (BMP) signalling during craniofacial development (Nimmagadda et al, 2015); LIN28Awhich may promote HMGA2 expression (Vignali & Marracci, 2020);…”
Section: Demographic Modelmentioning
confidence: 99%
“…ID2-which modulates bone morphogenetic protein (BMP) signalling during craniofacial development (Nimmagadda et al, 2015); LIN28Awhich may promote HMGA2 expression (Vignali & Marracci, 2020);…”
Section: Demographic Modelmentioning
confidence: 99%
“…HMGA1 is a member of the HMG family of architectural transcription factors and involved in chromatin remodeling and regulation of different gene expression depending on the cell context. [ 30 ]. HMGA1 is abundantly expressed during embryo development and downregulated in the adult differentiated tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It contains three special at‐hook structures, which can bind to at‐sequence‐enriched regions on DNA, promote or inhibit the expression of related target genes, and thus affect the development of embryos 5 . Generally, HMGA2 is only highly expressed at the early stage of fetal development, and the expression of HMGA2 can hardly be detected in normal adult tissues 6,7 . A large number of studies have shown that HMGA2 is highly expressed in most malignant tumors, and its expression level is closely related to the degree of malignancy and metastasis, including breast, melanoma, colorectal and bladder cancer 8,9 .…”
Section: Introductionmentioning
confidence: 99%